Bulgaria : Recent Economic Developments and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1999)
This paper reviews economic developments in Bulgaria during 1990-97. Bulgaria's macroeconomic performance during 1990-97 was weaker than in most transition countries in the region. With economic activity declining significantly during most years, the cumulative fall in real output over this period amounted to 37 percent. Although Bulgaria's difficult initial conditions and adverse external shocks played a role, the weak performance mainly reflected the stop-and-go nature of stabilization policies and the slow pace of structural reform.